Apexification: A Comprehensive Review - Nikita Samal (Institute of Medico-legal Publications Pvt Ltd, 2020)
Necrotic pulp in permanent teeth with incompletely formed or wide-open apices results in the death ofcells that are effective in the improvement of root. This slows down the possibility of apical closure aswell as improvement of root. Endodontic management consisting of diseased or dead pulp with adolescentpermanent teeth along with an open expanded root apex is a challenging concern. During obturation in thattooth,it is unimaginable to obtain a proper seal at the tip. There are various techniques to treat an immaturetooth with open apex which involve the application of (1) a custom-made cone(blunt end); (2) a short filltechnique; (3) periapical surgery; (4) apexification; and (5) one-visit apexification. Mostly recommendedtreatment of choice is ‘apexification’ which is a method to induce root apex development of an immaturenonvital tooth by formation of osteocementum or bone-like tissue. The most recommended medicament iscalcium hydroxide that facilitates the development of a calcific barrier found in the root apex. According tothe survey of the clinical involvement and information of journalists, management of an incomplete nonvitaltooth can bring noticeable outcomes from the disinfectant and ossification promoting activity of Ca(OH)2